IDENTIFICATION OF FUNCTIONAL GROUPS ORGANIC COMPOUNDS FROM RICE STRAW PULP BASED SPECTRA FTIR - Nasution, Zainal Abidin (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The purpose of research is conducted in the order to would have known determine of functional groups organic compounds contained by rice straw pulp treatment of the experimental results rice straw pulping. By identifying the functional groups of organic compounds through rice straw pulp FTIR spectrum of research results and then compare it with the image of standard cellulose FTIR spectra. And analyze with the framework of functional groups of organic compounds builder cellulose structure. Based on the experimental results pulp cooking rice straw treated with solution of cooked 2 % NaOH, 3 % NaOH and 4 % NaOH obtained average yields rice straw pulp is 49,28 %, 27,62 % and 24,39 %. Based on test results FTIR spectra of rice straw pulp known as much as 18 peaks the wavelength of functional groups of organic compounds, as shown in Table – 5. From the identification of the peak wavelength of functional groups organic compounds and compare it with the image of standard cellulose FTIR spectra, as shown in Table – 5 there were 11 peaks of functional groups of organic compounds which has a wavelength closes the wavelength approaches value of functional groups organics compound cellulose standard FTIR spectrum image. Of the 11 peaks of functional group organic compounds,there are as many 6 functional group of the organic compound cellulose structure of the skeleton builder wavelengths 2889,37 cm1 ; 1667,28 cm-1 ; 1431,18 cm-1 ; 1327,03 cm-1 ; 1249,87 cm-1 and 898,83 cm-1